'You look terrific!' Social evaluation and relationships in online compliments. (December 2013) - Maíz-Arévalo, Carmen; García-Gómez, Antonio
Despite its apparent simplicity, the speech act of complimenting has received a great deal of attention in the literature. However, studies have mostly focused on compliments' realization in face-to-face conversational exchanges, while they have often been neglected in other channels such as online communication. This article is intended to redress the balance in support of online exchanges. More specifically, we aim to investigate how users of online social networks like Facebook use compliments to evaluate others and strengthen social rapport in English and Spanish. In order to do so, we gathered two balanced corpora in both languages (50 examples in each language). The samples were quantitatively and qualitatively analysed using a systemic functional framework. The analysis reveals that compliments constitute a system of choices where several available options help Facebook users to encode their evaluation of the other from various perspectives (e.g. as an emotion, as an unquestionable truth, etc.). Furthermore, results also show that despite superficial similarities, compliments in both languages follow remarkably different frequencies of use which reflect deep cultural differences.